Firm Value With Dividend Policy As A Moderating Variable In Plantation Companies On The Indonesia Stock Exchange - Fitriani, Rachma Nur; Nur, Dhani Ichsanuddin (Jurnal Ekonomi, 2024)
This study aims to analyze the impact of profitability, liquidity, and leverage on company value, with dividend policy as a moderating variable, focusing on plantation companies listed on the Indonesia Stock Exchange for the 2018–2022 period. The research is grounded in the critical role that company value plays in attracting investors and ensuring long-term growth, particularly in the plantation sector, which significantly contributes to Indonesia's economy. Understanding the factors influencing company value is essential for developing strategies that enhance financial performance and sustainability. The population of this study comprised all plantation companies listed on the Indonesia Stock Exchange, with 11 companies selected as the sample. The data were analyzed using Moderated Regression Analysis (MRA) and processed through SPSS. The findings reveal that profitability positively influences company value, whereas liquidity and leverage do not have a significant effect. Moreover, dividend policy moderates the relationship between profitability and company value but does not moderate the relationships between liquidity or leverage and company value. These results highlight the importance of profitability and dividend policy in strengthening company value within the plantation industry.